THE EFFECT OF ADDITION OF TURMERIC FLOUR (Curcuma longa Linn) INFEED ON THE PERFORMANCE OF THE GROWTH AND IMMUNE SYSTEM OF FISH (Oreochromis niloticus) (Journal of Fish Health, 2022)
This study aims to determine tilapia's growth and immune system (Oreochromis niloticus) through feeding with added turmeric flour. This study used a completely randomized design with five treatments, namely K- (feed without adding turmeric flour and injected with physiological solution), K+ (feed without adding turmeric flour and injected with A. hydrophila bacteria), P1 (addition of turmeric flour 1 % / kg of feed + bacterial infection of A. hydrophilla), P2 (Addition of 2% turmeric flour/kg of feed + bacterial infection of A. hydrophilla), and P3 (Addition of 3% turmeric flour/kg of feed + bacterial infection of A. hydrophilla) each treatment had three replicates for a total of 15 trials. The results showed that there was a significant effect (p > 0.05) on growth but no significant effect (p < 0.05) on the survival of tilapia, so further tests were carried out to determine the best treatment in producing tilapia growth, it is known that P2 (Addition of 2% turmeric flour/kg of feed + bacterial infection of A. hydrophilla) is the best treatment in this study.
Keywords: immune system; growth; turmeric; tilapia